Current Limitations of Sentinel Node Biopsy in Vulvar Cancer - Myriam Gracia; Maria Alonso-Espías; Ignacio Zapardiel (Current Oncology)
Background: Vulvar cancer is a rare gynecologic malignancy with increasing incidence. Lymph node status is the most critical prognostic factor, traditionally assessed through inguinofemoral lymphadenectomy, a procedure associated with significant morbidity. Sentinel lymph node biopsy (SLNB), in selected cases, has emerged as a less invasive alternative with favorable oncologic outcomes. Objective: This review summarizes current evidence on the indications, technique, safety, and oncologic outcomes of SLNB in vulvar cancer, with a focus on controversial scenarios such as recurrent and larger tumors. Methods: A narrative review of PubMed-indexed studies published in English over the last 35 years was conducted. Eligible studies included original research, systematic reviews, meta-analyses, randomized controlled trials, and case-control studies. Results: SLNB is recommended for unifocal vulvar tumors < 4 cm with stromal invasion > 1 mm and clinically negative nodes. Landmark trials, including GROINSS-V-I and GOG-173, confirmed its accuracy and lower morbidity compared to lymphadenectomy. SLNB utilization has increased since its inclusion in guidelines, with a concurrent decline in lymphadenectomy rates. Combined detection techniques are mandatory, while indocyanine green (ICG) is an emerging option. Future studies should focus on refining patient selection criteria, improving detection techniques, and clarifying the implications of low-volume nodal disease to further optimize outcomes for patients with vulvar cancer. Conclusion: SLNB is a validated, minimally invasive staging approach in early-stage vulvar cancer. Further research is needed to refine its role in high-risk cases and optimize detection methods.